Marigold breeding in India: a comprehensive review of genetic advances, techniques and future prospects - D., Venkatesan; S., Ramesh Kumar (Frontiers in Plant Science, 2025)
Marigold (Tagetes spp.) is economically important flower crop widely cultivated for its vibrant flowers, use in religious ceremonies, landscaping, and extraction of carotenoids for industrial and pharmaceutical applications. Breeding advancements in marigold have primarily focused on enhancing yield, flower quality, and resistance to biotic and abiotic stresses. This review presents a comprehensive overview of progress in marigold breeding, covering traditional approaches such as selection, hybridization, and mutation breeding, as well as modern biotechnological tools, including marker-assisted selection (MAS), genomic selection, and CRISPR-based genome editing. Conventional breeding has led to the development of several high-yielding hybrids, including ‘Arka Abhi’ and ‘Arka Shubha,’ which are widely cultivated across India. Modern molecular approaches have facilitated the identification of quantitative trait loci (QTLs) associated with essential traits, improving the efficiency of breeding programs. In recent years, tissue culture techniques have played a pivotal role in the rapid propagation of elite varieties and the generation of somaclonal variants with desirable traits. Major challenges like a limited genetic base, climate change, pests and diseases still make sustainable production difficult. The integration of wild germplasm and advanced genomic tools offers promising avenues for addressing these limitations. Participatory breeding and interdisciplinary research play a crucial role in addressing location-specific demands and improving the economic viability of marigold cultivation. This analysis indicates the importance for sustainable breeding practices that match with growing market requirements and environmental issues. Hence, by integrating traditional knowledge with cutting-edge technologies, marigold breeding programs can unlock the crop’s full potential, contributing to the growth of India’s ornamental and agricultural sectors.